2020
DOI: 10.1056/nejmc2001573
|View full text |Cite
|
Sign up to set email alerts
|

A Locally Transmitted Case of SARS-CoV-2 Infection in Taiwan

Abstract: Situation Report-10 SITUATION IN NUMBERS Globally 7818 confirmed China 7736 confirmed 12167 suspected 1370 severe 170 deaths Outside of China 82 confirmed 18 countries WHO RISK ASSESSMENT China Very High Regional Level High Global Level High *The situation report includes information reported to WHO Geneva by 10 AM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 2 publications
2
110
0
6
Order By: Relevance
“…First, asymptomatic cases were diagnosed based on positive viral nucleic acid test results, but without any COVID-19 symptoms, such as fever, gastrointestinal, or respiratory symptoms, and no significant abnormalities on chest radiograph 7,8 However, the transmission of COVID-19 through asymptomatic carriers via person-to-person contact was observed in many reports. 4,7,9,10 cases were aged between 25 and 62 years. 16 Regarding elderly patients infected with SARS-CoV-2, one study showed that 14.6% (6 in 41) of patients were aged ≥ 65 years, 13 while another study showed that 15.2% (15 in 99) patients were aged ≥ 70 years, among pneumonia cases.…”
Section: Severity Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…First, asymptomatic cases were diagnosed based on positive viral nucleic acid test results, but without any COVID-19 symptoms, such as fever, gastrointestinal, or respiratory symptoms, and no significant abnormalities on chest radiograph 7,8 However, the transmission of COVID-19 through asymptomatic carriers via person-to-person contact was observed in many reports. 4,7,9,10 cases were aged between 25 and 62 years. 16 Regarding elderly patients infected with SARS-CoV-2, one study showed that 14.6% (6 in 41) of patients were aged ≥ 65 years, 13 while another study showed that 15.2% (15 in 99) patients were aged ≥ 70 years, among pneumonia cases.…”
Section: Severity Of Covid-19mentioning
confidence: 99%
“…To date, COVID-19 has affected people in more than 28 countries/regions, including Taiwan, and has become a global threat. [1][2][3][4] In addition, the Coronavirus Study Group of the International Committee on Taxonomy of Viruses has renamed the virus, which was provisionally named 2019-nCoV, as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) based on phylogeny, taxonomy, and established practice. 5 Prior to this, on January 30, 2020, the WHO declared the COVID-19 outbreak as the sixth public health emergency of international concern; therefore, this outbreak constitutes a public health risk through the international spread of disease and requires a coordinated international response.…”
Section: Introductionmentioning
confidence: 99%
“…The second phase started on January 13, marked by rapid expansion and spread of the virus within hospitals (nosocomial infection) and by family transmission (close-contact transmission). In this phase the epidemic spread from Wuhan to other areas [12][13][14][15][16][17][18]. The first case outside of China was reported in Thailand on January 13, caused by a Wuhan resident travelling to this country.…”
Section: Epidemiology Of Covid-19mentioning
confidence: 99%
“…The infected patients were generally presented with mild upper respiratory infection symptoms similar to the common cold at the early stage and could be afebrile on the first 1-2 days Del Rio and Malani, 2020;Heymann and Shindo, 2020;Holshue et al, 2020;Rothe et al, 2020;The Novel Coronavirus Pneumonia Emergency Response Epidemiology Team, 2020;Xu et al, 2020e;Yang et al, 2020a,b). Common symptoms included fever (88-98%), fatigue, dry cough, upper airway congestion, sputum production, shortness of breath, myalgia/arthralgia, and gastrointestinal symptoms (Chan et al, 2020b;Chang et al, 2020;Chen et al, 2020a;Del Rio and Malani, 2020;Guan et al, 2020;Holshue et al, 2020;Liu et al, 2020b;Pan et al, 2020;Pongpirul et al, 2020;Wang et al, 2020a;Xu et al, 2020c;Yang et al, 2020b;Yao et al, 2020;Zhang et al, 2020a;Zhu et al, 2020) with lymphopenia, prolonged prothrombin time, elevated C-reactive protein, and elevated lactate dehydrogenase (LDH) (Chan et al, 2020b;Chen et al, 2020a;Guan et al, 2020;Holshue et al, 2020;Liu et al, 2020a;Wang et al, 2020a). Chest computed tomographic showed bilateral patchy shadows or ground glass opacity (Bernheim et al, 2020;Chan et al, 2020b;Chang et al, 2020;Guan et al, 2020;Holshue et al, 2020;Pan et al, 2020;Wang et al, 2020a;Zhu et al, 2020).…”
Section: Clinical Presentationmentioning
confidence: 99%